(untitled) (American Journal of Interdisciplinary Research and Development, 2022)
Plays an important role in fatty liver. Fats that get into the liver are released from their fats as a source of energy. Exogenous (external) fats fall from the intestine through the lymph into the general circle of blood circulation. These are mainly uchasylglycerides, which are absorbed undisturbed, and it falls into the liver in the case of high fat content, which has not been used in the biosynthesis of fats and phosphatides in the intestinal wall.